Kesatuan dan Perbedaan dalam Gereja Perdana - Victor Christianto (Asosiasi Teolog Indonesia, 2014)
Two interesting questions in relation to the Early Church history are the extent of unity or diversity among Peter, James, and Paul; and also how Paul's thoughts have shaped the direction of the Church in later periods. Answers to these questions will be very helpful in order that we can give a proper response to